2020
DOI: 10.1177/2164956120916176
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties Perceived by ICU Nurses Providing End-of-Life Care: A Qualitative Study

Abstract: Background: With advances in medicine and technology, intensive care units (ICUs) have the capacity to treat patients who would have previously not been expected to survive and would therefore not have been managed in ICUs. When an individual is not expected to survive, doctors and nurses face the modern ethical dilemma of death associated with withdrawal of life-supporting strategies. The aim of this study was to identify difficulties perceived by ICU nurses providing endof-life care (EOLC) in Poland. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…In this study, participants reported some challenges and difficulties when communicating with the family of dying patients. These results are consistent with the results of previous studies (Aslakson et al, 2012;Crump, Schaffer, & Schulte, 2010;Muni et al, 2011;Ozga et al, 2020). There are several factors that can create challenges and have an impact on the quality and quantity of communication between doctors, patients, and families at the end-of-life in the ICU.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, participants reported some challenges and difficulties when communicating with the family of dying patients. These results are consistent with the results of previous studies (Aslakson et al, 2012;Crump, Schaffer, & Schulte, 2010;Muni et al, 2011;Ozga et al, 2020). There are several factors that can create challenges and have an impact on the quality and quantity of communication between doctors, patients, and families at the end-of-life in the ICU.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, most of EOLC provided by nurses was focused on family. Some studies state that EOLC in the ICU is challenging (Kisorio & Langley, 2016;Ozga et al, 2020). Ozga et al (2020) identified three categories of potential barriers in providing EOLC, namely (1) barriers attributable to the hospital, (2) barriers related to the patient's family, and (3) barriers related to the ICU personnel providing direct EOLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brooks and colleagues 52 noted a lack of timely discussions and multidisciplinary acceptance of EOL plans. Ozga et al 53 reported a lack of professional collaboration and limitations of hospital managers as the main barriers to implementing EOL care in the ICU. Flannery and colleagues 54 reported role ambiguity and lack of opportune discussions about EOL care as great clinical challenges.…”
Section: Emotional Impactmentioning
confidence: 99%
“…Nurses' attitudes and behaviors about death affect the quality of care in the end-of-life process. [6][7][8][9][10] Therefore, it is of great importance to determine the attitudes and behaviors of intensive care unit nurses who frequently encounter patients in the last days of life. The aim of our study is to determine the attitudes and behaviors of intensive care unit nurses towards end-of-life care.…”
Section: Introductionmentioning
confidence: 99%